Fecal Microbiota and Human Intestinal Fluid Transplantation: Methodologies and Outlook - Chen, Ye; Zhiliang, Lin; Jiaqu, Cui; Xiaoqiong, Lv; Shaoyi, Zhang; Chunlian, Ma; Yinmei, Yan; Bo, Yang; Di, Zhao; Hongliang, Tian; Ning, Li; Qiyi, Chen; et al. (Frontiers in Medicine, 2022)
Fecal microbiota transplantation (FMT) is a therapy that involves the transplantation of healthy human fecal microorganisms into the gut of patients to rebuild or consolidate the intestinal microecology. It has been utilized in many diseases. However, FMT had a limited effect on patients with small intestinal diseases because of the unique ecological characteristics of the microorganisms. Thus, we proposed a new microecology transplantation therapy called human intestinal fluid transplantation (HIFT). Human intestinal fluid can be collected through a nasojejunal tube and be made into capsules using the freeze-dried powder method. In addition, strict standards for donor screening and management have been established. We are looking forward to developing a high-standard HIFT preparation system and conducting high-quality clinical studies to validate the safety and efficacy of HIFT combined with FMT.